Educational migration in Eurasia: new trends (International relations and international law Journal, 2018)
International educational migration is becoming more intense in the modern world. The article presents the analysis of educational migration in the Eurasian space, are defined new attraction centers of educational migration in the region. Systematization of theoretical approaches to the study of this process and research of trends in migration movements allowed the author to identify the features of educational migration in the region. Significant attention is paid to the factors influencing the migration plans of students, the consequences of educational migration. Based on the analysis, a conclusion is made about the opportunities and consequences of educational migration, the fact that today there is a intense competition between the world’s educational centers for attracting and retaining educational migrants. The authors pay attention to the consideration of educational migration, both from the point of view of a positive phenomenon and from the point of view of the negative phenomenon. Based on the analysis, a conclusion was made about the possibilities and consequences of educational migration, the fact that today there is a sharp competition between the world’s educational centers for attracting and retaining educational migrants. The authors have identified the contribution of the countries of the Eurasia region to the formation of migration flows, and new centers for the attraction of educational migrants have been identified.Key words: educational migration, educational migrants, education market, Eurasia, Kazakhstan.